A Comprehensive Review of Probiotic Mechanisms and Their Implementation in Gastrointestinal Health Management - Yunita Kristina; Ipah Kurnia Putri (CV. Get Press Indonesia, 2025)
Probiotics, which are live microorganisms that benefit the host, have been shown to be effective in preventing and treating antibiotic-associated diarrhea (AAD). However, the specific molecular mechanisms of individual probiotic strains remain poorly understood. This study aims to explore strain-specific approaches for managing gastrointestinal disorders and to provide a scientific overview of the benefits and mechanisms of probiotics in maintaining and improving gut health through complex and interconnected pathways. A systematic literature search was conducted using keywords such as “probiotics,” “gut microbiota,” “strain-specific mechanisms,” “gastrointestinal health,” “host-microbe interaction,” and “synbiotics,” across reputable databases including PubMed, Scopus, ScienceDirect, and Google Scholar. The methodological quality and strength of evidence for each study were assessed using the GRADE (Grading of Recommendations, Assessment, Development and Evaluation) framework. Numerous studies have confirmed that probiotics help prevent and treat AAD and may also reduce the risk of irritable bowel syndrome (IBS) and inflammatory bowel diseases. Clinical trials have also shown promising results regarding the ability of various probiotic strains to balance the mucosal immune system and gut microbiota. However, comprehensive research on the synergistic interactions between probiotic and prebiotic strains remains limited. Therefore, future studies should focus on cross-omic approaches, exploration of local strains from traditional diets, and personalized strategies to optimize the efficacy of probiotics in supporting gastrointestinal health.